Intégration des immigrés et associations en France. Un essai d’approche croisée par l’économie et la géographie - William Berthomière; Mathilde Maurel; Yann Richard (Cybergeo, 2015)
The issue of integration is key in the literature about migration. It refers to a set of public policies aiming at integrating foreign populations in a given society. This paper aims at investigating the relationships between the integration of four communities settled in France (Algerian, Portugese, Turkish, and Vietnamese) and the presence of associations. The methodology is based on two approaches, quantitative economics and geography. It uses a new database, extracted from the Journal Officiel and several surveys, noticeably TeO. In a first step we ask whether the regional distribution and the density of associations explain the degree of integration of the migrants stemming from the four communities. In a second step we test whether membership in an association increases or decreases the adoption of oppositional identities and if the latter influences the integration via the access to employment.